Binary solvent participation in crystals of a multi-aromatic 1,2,3-triazole - Jonathan Filley (Acta Crystallographica Section E: Crystallographic Communications)
The X-ray crystal structure of a multi-aromatic substituted 1,2,3-triazole is presented, which shows an extensive three-dimensional hydrogen-bonding network involving two water molecules and two acetonitrile molecules. The structure of 4-{[(4-{[1-({[(3,4-dimethoxyphenyl)methyl](3-acetamidophenyl)carbamoyl}methyl)-1H-1,2,3-triazol-4-yl]methoxy}-3-methoxyphenyl)methyl]amino}benzoic acid–acetonitrile–water (1/2/2), C37H38N6O8·2C2H3N·2H2O, features amine-linked aromatic groups that have a variety functionality including a carboxylic acid, an acetamido group, and methoxy ethers. All X—H groups, and seven out of ten heteroatoms with available lone-pair electrons, participate in hydrogen bonding, with the aid of dimer-bridging water molecules and acetonitrile molecules whose methyl groups form close contacts with oxygen atoms. The triazole itself is a dimer made using click chemistry from readily available and inexpensive starting materials and is a precursor to larger oligomers, as well as to compounds with a wide array of readily manipulated functionality.